Biology and shell relationship in Clibanarius vittatus (Bosc, 1802) (Crustacea, Diogenidae) from Sao Vicente, SP, Brasil. - Reigada, ALD; Santos, S. (Inst Tecnologia Parana, 1997)
This study aimed to characterize the populational structure of Clibanarius vittatus (Bosc, 1802), as well as to determine the morphometric relations between the animal's size and the variables: length of their chelar propodus and the size of the shell opening. C. vittatus is a relatively abundant pagurid on the west Atlantic coast, it occurs in the intertidal region from 38 degrees N to 28 degrees S. The animals in this study were randomly sampled every month on the Paranapu (a) over tilde Beach (46 degrees 23' S e 23 degrees 59' W), S (a) over tilde $ o Vicente (SP), Brazil. The biometrics data were adjusted to the power equation (y = ax(b)), by means of the minimum square method. A total of 427 individuals were collected. The size of the cephalothoraxic shield ranged from 2.5 to 12.7 mm, evidencing a representative sample of the population. The of most commonly genus of Gastropoda shells occupied by the hermits was Thais (97,26%). In relation to the morphometric analyses performed, it was observed a positive correlation between the animal size and the variables length of the chelar propodus and the size of the shells.
Keywords: Paguridae; Clibanarius; populational; biology; morphometric